Sensory gating, habituation, and orientation of P50 and N100 event-related potential (ERP) components in neurologically typical adults and links to sensory behaviors - Greife, Catherine L., author; Davies, Patricia, advisor; Atler, Karen, committee member; Gavin, William, committee member; LaGasse, Ashley B., committee member (Colorado State University. Libraries, 2013)
This thesis project used a novel electroencephalography (EEG) auditory paradigm, the orientation/habituation paradigm, to understand brain processing in response to multiple auditory stimuli. This paradigm allowed the exploration of several neurological processes within one task: sensory gating, orientation to deviant stimulus, and habituation and dishabituation. Sensory gating has been studied extensively in individuals with neurological disorders (Arnfred & Chen, 2004; Boutros, Belger, Campbell, D'Souza, & Krystal, 1999; Kisley et al., 2003) and there are a few studies that have examined habituation and orientation in individuals with epilepsy or schizophrenia (Rosburg et al., 2004; Rosburg et al., 2006; Viswanathan & Jansen, 2010). The construct of dishabituation, referring to the brain's processing of standard stimuli after the presentation of a deviant stimulus, has not been studied previously. In addition to exploring these neurological phenomena, this project investigated the relationship between brain processing and scores on sensory behavioral inventories, the Adolescent/Adult Sensory Profile (Brown & Dunn, 2002) and the Sensory Gating Inventory (Hetrick, Erickson, & Smith, 2012). Participants were 38 neurologically typical adults (average age 19.6 ±1.46 years). These adults demonstrated significant sensory gating from stimulus 1 to stimulus 2 at all electrode sites (p < .0005). There was also a significant orientation effect of P50 and N100 to the deviant stimuli. There was no habituation of the P50 ERP component over time and there were mixed results regarding whether or not the P50 was dishabituated when a deviant tone was presented. In contrast to the P50, there were significant linear trends found for N100 at four of the five electrode sites, demonstrating habituation. Additionally, when presented with a deviant stimulus in the middle of a series of standard stimuli, N100 was not dishabituated, and in some cases demonstrated significant increase in habituation after the deviant stimulus. These results indicate that there is some sort of cognitive control over the suppression of the N100 amplitude that is not seen for the suppression of P50. Finally, when correlated with sensory behavior tasks, sensory gating of N100 amplitude was significantly associated with Sensation Avoiding on the Adolescent/Adult Sensory Profile (A/ASP) (Brown & Dunn, 2002). Increase in P50 amplitude to the deviant stimulus, reflecting orientation, was significantly negatively correlated with both Over-Inclusion and Fatigue and Stress Vulnerability of the Sensory Gating Inventory (Hetrick, Erickson, & Smith, 2012) and positively with the Sensation Seeking quadrant of the A/ASP. Increase in N100 amplitude to the deviant stimulus, reflecting orientation, was significantly related to the Touch Processing subscale of the A/ASP.
Keywords: sensory behaviors; sensory gating; event related potentials; habituation; orientation